Assessing Anxiety in the Cardiac Catheterization Pathway: Cross-Sectional Evidence from a Tertiary Center - Ahmed, Atheer Abd (Universitas Muhammadiyah Sidoarjo, 2025)
Anxiety is a common response to stressful medical interventions. Patients undergoing cardiac catheterization frequently experience heightened anxiety due to fear of pain, complications, or an unfavorable diagnosis. Assess anxiety levels among patients undergoing cardiac catheterization and to examine their relationship with selected demographic variables. Cross-sectional study of 100 patients at Mosul Center for Cardiology and Cardiac Surgery. Data on anxiety were collected via interview questionnaires and analyzed in SPSS v28. Purposive sampling was used. Study period: 13 October 2024–20 April 2025. Fifty percent of patients had moderate anxiety. Anxiety correlated positively with gender (r=0.240, p=0.016) and negatively with educational level (r=−0.198, p=0.048) and occupation (r=−0.335, p<0.001). Most patients reported moderate anxiety. Gender and education showed weak but significant correlations with anxiety, while occupation showed a moderate negative correlation. Targeted mental-health programs and improved access to psychological services are recommended. Highlights: Moderate to severe anxiety was present in 80% of patients undergoing cardiac catheterization, with fear being the most dominant symptom. Anxiety showed significant associations with gender, education, and occupation, but not with medical comorbidities. Findings emphasize the need for routine anxiety screening and targeted psychosocial interventions in catheterization care.